Extrusion Expansion Characteristics of Samples of Select Varieties of Whole Yellow and Green Dry Pea Flours. Issue 3 (11th October 2016) - Li, Chongjun; Kowalski, Ryan J.; Li, Lei; Ganjyal, Girish M.
Abstract : Extrusion expansion characteristics of commercially available whole flours from three green pea varieties (Ariel, Aragorn, and Daytona) and three yellow pea varieties (Carousel, Treasure, and Jetset) were investigated with a corotating twin‐screw extruder. Feed moisture content was kept constant at 15 ± 0.5% (wb). Two barrel temperature levels of 140 and 160°C and three screw speed levels of 150, 200, and 250 rpm were studied. A round die with an opening of 3 mm was used. The radial expansion ratio (ER) of whole pea extrudates was 2.75–3.34. It was shown that the varieties had a significant impact on the expansion properties. Daytona green pea had a significantly greater ER compared with all other varieties ( P < 0.05) within the conditions studied. ER was also found to have a positive linear correlation with screw speed. The microstructure of extrudate cross‐sections showed that the samples with greater expansion had more uniform and relatively small pore structure. The results show the importance of using the specific varieties of peas for optimum expansion during extrusion.